Ameliorating effect of L-Cysteine on lead acetate-induced hepatotoxicity and nephrotoxicity in male mice - Abd El-Ghffar, Eman Ali; El-Aal, Ali Abd (Progress in Nutrition, 2018)
Lead poisoning is one of the most common environmental pollutant and potential danger to human health. Here, we evaluated and compared the possible therapeutic potentials of two different doses of L-Cysteine and EDTA chelating agent against lead acetate induced hepatotoxicity and nephrotoxicity in mice. Thirty male mice were divided into seven groups (n=6): Group I, (normal control); Group II, (control treated): mice were injected intraperitoneal (i.p.) with L-Cysteine at a dose 40 mg/kg body weight (b.wt); Group III, (control treated): mice were injected i.p. with L-Cysteine at a dose 80 mg/kg b.wt; Group VI, (lead-acetate treated): mice were injected i.p. with lead acetate at a dose 40 mg/kg b.wt; Group V, (lead-acetate + CaNa2EDTA 50): mice were injected i.p. with lead acetate followed by treatment with CaNa2EDTA; Group VI, (lead-acetate + L-Cysteine 40): mice were injected i.p. with lead acetate followed by treatment with L-Cysteine; Group VII , (lead-acetate + L-Cysteine 80). This study reported that only the high dose of L-Cysteine 80 significantly alleviated (P < 0.05–0.001) all complications shown in intoxicated mice, including body weight loss, changes in weights of organs, elevation in serum Pb, glucose and markers of liver and kidney functions. The antioxidant activity of the high dose of L-Cysteine 80 was comparable (P > 0.05) with that of CaNa2EDTA (77.93 versus 75.78%, respectively) and mediated by significantly decreasing hepatic/renal lipid peroxidation and increasing hepatic/renal GSH concentrations. The present study proved L-Cysteine showed effective anti-oxidative action against lead acetate-induced hepatotoxicity and nephrotoxicity in mice in a dose-dependent manner.